DEVELOPMENT STRATEGIES OF CREATIVE CITY (CASE STUDY: SHIRAZ) - Alireza Pourbagheri; Masoud Taghvaei; Vachik Hairapetian (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The approach of the creative city theory is a response to the changes in the cities, especially the social evolutions, which depend on the globalization phenomenon. In these cities, it is attempted to focus on the local and international cultures in the social and economic issues as a response to globalization. The current study aimed to find strategies for the development of creative city in Shiraz, which was done based on the analyticaldescriptive method. The current research was applied research. The survey study based on the questionnaire and library study was used to collect the data. Statistical methods and SPSS software were used to analyze the data and test the hypotheses. Also, in the second phase of the research, the SWOT method was utilized to codify the strategies of the urban development, and the QSPM matrix was used to prioritize. The general conclusion based on the perspective of all societies (local people, experts, and officials) on four physical, ecological, sociocultural, economic-tourism, and organizational management aspects in the development of the creative city in Shiraz indicated that two groups of societies (experts and officials) considered the economic perspective the most effective factor. Therefore, according to the conducted analyzes of all societies, in summary, the economic factor was introduced as the most influential factor in the development of the creative city in Shiraz. Based on the analytical model of the strategies, such as training specialized and expert forces in the creative city, defining prospects and policies of the employment with the creative approach and improvement of the cultural and social role of Shiraz city, considering its historical background, were presented as immediate strategies, and other strategies were offered as midterm and long-term strategies. In the end, some executive measurements were recommended for the development of the creative city in Shiraz.